THERMAL DIFFUSIVITY OF ALUMINOUS SPINELS AND MAGNETITE AT ELEVATED TEMPERATURE WITH IMPLICATIONS FOR HEAT TRANSPORT IN EARTH'S TRANSITION ZONE - Hofmeister A.M. (My University, 2007)
The phonon component of thermal diffusivity (D) from 12 single crystals in the spinel family was measured at temperatures (T) of up to ~2000 K, using laser-flash analysis. Synthetic disordered spinel, 4 gemstones near MgAl2O4, nearly ZnAl2O4 "hercynites" [(Mg,Fe 2+1) (Al, Fe3)2O4], and 2 magnetites (nearly Fe3O4) were characterized using optical spectroscopy and electron microprobe analysis. The magnetic transition in Fe3O4 is manifest as a lambda curve in 1/D, but otherwise, D decreases with increasing T and approaches a constant (Dsat) at high T. Part of the decrease in D as T increases results from disordering above ~700 K: these two effects were distinguished by making multiple heating runs. At 298 K, D decreases strongly as either cation substitution or Mg-Al disorder increases, whereas Dsat is moderately perturbed by substitutions. For both ordered and (equilibrium) disordered spinels and hercynites, the temperature dependence of 1/D is best described by low-order polynomial fits. For spinel, combining our data with previous cryogenic studies of thermal conductivity (k) constrains the T dependence of D and k from ~0 K to melting. The response of D to disorder, impurity content, and cation mass for the aluminates is used to constrain D(T) for γ-Mg2SiO4 and ringwoodite. Pressure derivatives are provided by relationships such as ∂ln (klat)/∂P = ∂ln(KT)/∂P. Our results show that the phonon contribution to heat transport in Earth's transition zone is high, particularly for large proportions of ringwoodite.
Keywords: ALUMINATES; HIGH PRESSURE; HIGH TEMPERATURE; IR SPECTROSCOPY; LASER-FLASH METHOD; SPINEL-FAMILY MINERALS; THERMAL DIFFUSIVITY